On the Use of a Water Potential Probe for Suction and Temperature Measurements in Unsaturated Natural Clayey Soil - Nico Stasi; Vito Tagarelli; Osvaldo Bottiglieri; Francesco Cafaro (Applied Sciences)
The accurate measurement of soil suction is essential for understanding the behavior of unsaturated soils, particularly in soil–vegetation–atmosphere (SVA) interactions, where both energy and hydraulic gradients due to climatic action exhibit their maximum intensity. This study assesses the performance of the TEROS 21 probe, a capacitance-based water potential sensor, for measuring soil matric suction and temperature in clayey soils of the South Apennines, Italy. Laboratory tests were conducted on soil samples with varying moisture contents, and the results were compared with those obtained using the traditional filter paper (FP) method and high-capacity tensiometers (HCTs). The TEROS 21 (METER Group, Inc., Pullman, WA, USA) sensor demonstrated a reliable performance, especially at suction levels between 300 and 2000 kPa, though there was some dependency on the initial sensor conditions (wet or dry). The temperature data obtained from the TEROS 21 were verified by using a thermocouple, showing the high consistency of the readings. This study showed that the filter paper and sensor measurements aligned at a water content lower than 30% but diverged at higher levels due to method-specific accuracy limitations. The consistent sensor results confirmed the measurement’s reliability. The air-entry value (AEV) of the soil water retention data was identified at around 800 kPa, which is consistent with previous findings.